Climate-based Genotype x Environment Interaction Study and Stability Analysis in Half-Sib Families of Grevillea robusta - Bhandari, Maneesh S.; Dabral, Aman; Kant, Rama; Meena, Rajendra K.; Pandey, Shailesh (Indian Forester, 2024)
The genetic evaluation of CPTs using multi-environment trials is to understand the genotype × environment interaction (G×E), which is an important step in tree improvement programmes. A method determining the performance of half-sib is based on adaptability and stability (G×E interaction).Candidate Plus Trees (CPTs) of potentially exotic agroforestry species, i.e., Grevillea robusta has been selected based on Index method. A set of six half-sib families (HSFs) each with multi-location trials in two consecutive years, i.e., 2018-19 and 2019-20 has been conducted in four different environments. The correlation and growth performance of HSFs with a past climatic variables that are supposed to have a significant effects on the growth and performance of HSFs were also analysed. Herein, we classified unfavourable and favourable environments with an ideal climatic condition for G. robusta adaptability and stability. The results revealed that, HSF1.2 (2018-19) and HSF2.3 (2019-20) were found to be highly adaptive and 1.2 2.3 promising for all the characters especially to obtain timber-yield, across the different environments. The environmental variables, namely soil moisture and precipitation plays critical role in the growth performance of the established trials. The implications of G×E interaction study were to understand the behaviour of CPTs in multi-environments. Thus, provide information on the best suitable climatic conditions for G. robusta and any tree species, especially when forest geneticists desire to quantify the adaptability and stability of the genotypes.